Percutaneous coronary intervention in nonagenarians: pros and cons - Biondi Zoccai, Giuseppe; Abbate, Antonio; D'Ascenzo, Fabrizio; Presutti, Davide; Peruzzi, Mariangela; Cavarretta, Elena; Marullo, Antonino G M; Lotrionte, Marzia; Frati, Giacomo (Journal of geriatric cardiology : JGC, 2013)
Percutaneous coronary intervention is a mainstay in the management of symptomatic or high-risk coronary artery disease. The bulk of clinical evidence and experience underlying this fact relies, however, on relatively young patients. Indeed, few data of very limited quality are available which adequately define the risk-benefit and cost-benefit profile of coronary angioplasty and stenting in very old subjects, such as those of 90 years of age or older (i.e., nonagenarians). The aim of this review is to provide a concise, yet practical, synthesis of the available evidence on percutaneous coronary revascularization in the very elderly. The main arguments elaborated upon are to what extent we can extrapolate findings from studies including younger patients to nonagenarians, whether we should provide higher priority to prognosis or quality of life in such patients, and whether we can afford to allocate vast resources to care for such subjects in an era of financial constraints. Our review of 18 studies and 1082 patients suggest that percutaneous coronary intervention is feasible and associated with acceptable short- and long-term results in this population, which is nonetheless fraught with a high mortality risk irrespective of the revascularization procedure. Accordingly, the pros and cons of percutaneous coronary intervention should be carefully weighed when considering this treatment in nonagenarians.